Risk of seizures and status epilepticus in older patients with liver disease. (6th June 2018) - Alkhachroum, Ayham M.; Rubinos, Clio; Kummer, Benjamin R.; Parikh, Neal S.; Chen, Monica; Chatterjee, Abhinaba; Reynolds, Alexandra; Merkler, Alexander E.; Claassen, Jan; Kamel, Hooman
Summary: Objective: Seizures can be provoked by systemic diseases associated with metabolic derangements, but the association between liver disease and seizures remains unclear. Methods: We performed a retrospective cohort study using inpatient and outpatient claims between 2008 and 2015 from a nationally representative 5% sample of Medicare beneficiaries. The primary exposure variable was cirrhosis, and the secondary exposure was mild, noncirrhotic liver disease. The primary outcome was seizure, and the secondary outcome was status epilepticus. Diagnoses were ascertained using validated International Classification of Diseases, Ninth Edition, Clinical Modification codes. Survival statistics were used to calculate incidence rates, and Cox proportional hazards models were used to examine the association between exposures and outcomes while adjusting for seizure risk factors. Results: Among 1 782 402 beneficiaries, we identified 10 393 (0.6%) beneficiaries with cirrhosis and 19 557 (1.1%) with mild, noncirrhotic liver disease. Individuals with liver disease were older and had more seizure risk factors than those without liver disease. Over 4.6 ± 2.2 years of follow‐up, 49 843 (2.8%) individuals were diagnosed with seizures and 25 patients (0.001%) were diagnosed with status epilepticus. Cirrhosis was not associated with seizures (hazard ratio [HR] = 1.1, 95% confidence interval [CI] = 1.0‐1.3), but there was an association with status epilepticus (HR = 1.9, 95% CI = 1.3‐2.8). Mild liver disease was not associated with a higher risk of seizures (HR = 0.8, 95% CI = 0.6‐0.9) or status epilepticus (HR = 1.1, 95% CI = 0.7‐1.5). Significance: In a large, population‐based cohort, we found an association between cirrhosis and status epilepticus, but no overall association between liver disease and seizures.